Analisa Bisnis Model Canvas Pada Usaha Jasa Layanan Kebersihan Fast Clean - Lukman Hakim (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
Businesses must adapt and innovate quickly because the corporate world is very dynamic. This is especially true for MSMEs, which make up a large share of Indonesia's GDP. The FastClean cleaning app uses digital technology to make ordering and payment easier. In this article, the Business Model Canvas (BMC) is used to build the FastClean business model. The FastClean Business Model offers customizable cleaning services for customers who have busy lifestyles. Professionalism, quality of service, ease of booking, and affordable prices are the advantages offered. FastClean uses a variety of channels, including customer reviews, social media apps, and paid advertising.